Low-carbon wall material for garden buildings and preparation method of low-carbon wall material
By using environmentally friendly materials such as plant fibers and recycled aggregates, combined with functional additives such as aerogel microspheres and photocatalytic materials, a low-carbon wall material with multifunctional properties has been prepared, which has solved the problem of existing materials in low-carbon The shortcomings in environmental protection, versatility and aesthetics have achieved efficient energy conservation and environmental protection.
Patent Information
- Application Number
- CN202411598880.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing garden building wall materials have shortcomings in low-carbon environmental protection, versatility, resource recycling and aesthetics, and it is difficult to meet environmental protection and functional needs at the same time. At the same time, the treatment of construction waste is also an urgent problem to be solved.
A low-carbon wall material is used, including plant fibers, recycled aggregates, environmentally friendly binders, low-carbon additives, waterproofing agents, aerogel microspheres, photocatalytic materials, negative ion generation materials, and degradable polymer fibers. Shape memory alloy fibers, phase change energy storage materials, microbial curing agents and intelligent moisture regulating materials, make wall materials with multifunctional properties through specific mixing and processing steps.
It has achieved low-carbon environmental protection, versatility and aesthetics, and has significant thermal insulation performance, air purification function, negative ion release capability, temperature regulation and humidity regulation functions, and has good mechanical properties and durability. It can effectively reduce energy consumption and carbon emissions.
Smart Images

Figure BDA0005127713490000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a low-carbon wall material for a garden building and a preparation method thereof. Background Art
[0002] With the increasing attention paid to environmental protection and sustainable development around the world, the low-carbon development of the construction industry has become an inevitable trend. In the field of garden architecture, wall materials are an important component, and their low-carbon transformation is of key significance for reducing building energy consumption and carbon emissions.
[0003] Traditional garden building wall materials mainly have the following problems. On the one hand, the large-scale use of traditional materials such as solid clay bricks not only consumes a lot of land resources, but also emits a large amount of greenhouse gases such as carbon dioxide during the firing process, causing serious pollution to the environment. On the other hand, although some existing wall materials have taken environmental factors into consideration to a certain extent, they still have problems of single function and insufficient performance. For example, ordinary aerated concrete blocks and other materials, although relatively low-carbon in the production process, have limited thermal insulation performance, resulting in high energy consumption in garden buildings during use, which is not conducive to energy conservation.
[0004] In modern garden architecture, people have higher and higher requirements for wall materials. In addition to the basic structural support function, they are also expected to have a variety of environmentally friendly and functional characteristics. For example, with the prominence of air quality issues, people hope that wall materials can have a certain ability to purify pollutants in the air; at the same time, in order to improve the comfort of indoor and outdoor environments, the humidity and temperature regulation functions of wall materials have also attracted much attention. However, it is difficult for wall materials on the market to meet these diverse needs at the same time.
[0005] From the perspective of material sources, the treatment of construction waste is also an urgent problem to be solved. A large amount of construction waste such as abandoned concrete and bricks occupies a large amount of land resources, and improper treatment may cause secondary pollution to soil and water sources. If these construction wastes can be reasonably recycled and reused to make garden building wall materials, it will be an effective way to achieve resource recycling and reduce carbon emissions.
[0006] In addition, with the development of garden architecture design concepts, new requirements have been placed on the plasticity and aesthetics of wall materials. The limitations of traditional materials in shape and appearance limit the artistic expression of garden architecture. Therefore, the development of a new type of low-carbon wall material for garden buildings, taking into account low-carbon environmental protection, multifunctionality, resource recycling and aesthetics, has become an urgent need for the sustainable development of the garden architecture industry. The low-carbon wall material and preparation method for garden buildings proposed in this patent are intended to solve the above problems and provide a more advantageous wall material solution for the field of garden architecture. Summary of the invention
[0007] 1. Technical issues to be solved
[0008] In view of the deficiencies in the prior art, the present invention provides a low-carbon wall material for a garden building and a preparation method thereof.
[0009] (II) Technical solution
[0010] A low-carbon wall material for a garden building comprises the following raw materials in parts by weight:
[0011] 20-40 parts of plant fiber, 30-50 parts of recycled aggregate, 10-20 parts of binder, 5-15 parts of low-carbon additive, 2-8 parts of waterproofing agent, 3-8 parts of aerogel microspheres, 2-6 parts of photocatalytic material, 3-7 parts of negative ion generating material, 5-10 parts of degradable polymer fiber, 2-5 parts of shape memory alloy fiber, 3-6 parts of phase change energy storage material, 2-5 parts of microbial curing agent, 3-8 parts of intelligent humidity control material;
[0012] The plant fiber has a length of 3-10 mm and is selected from one or more of hemp fiber, bamboo fiber and straw fiber;
[0013] The particle size of the recycled aggregate is 0.5-5 mm, and it is made by crushing waste concrete and bricks;
[0014] The binder is an environmentally friendly inorganic binder, selected from one or more of water glass and phosphate binders;
[0015] The low-carbon additive is biomass carbon powder, the particle size of which is less than 0.1 mm and the specific surface area is 200-500 m 2 / g.
[0016] The waterproofing agent is an organosilicon waterproofing agent;
[0017] The aerogel microspheres have a particle size of 0.5-2 mm, a porosity of 80-95%, and are mainly composed of silicon dioxide aerogel;
[0018] The photocatalytic material is a mixture of nano titanium dioxide and zinc oxide, the mass ratio of the two is 1-3:1, and the particle size is 20-50nm;
[0019] The negative ion generating material is tourmaline powder with a particle size of 1-5 μm;
[0020] The degradable polymer fiber is polylactic acid fiber with a diameter of 0.1-0.3 mm;
[0021] The shape memory alloy fiber is a nickel-titanium alloy fiber with a diameter of 0.05-0.2 mm, which has a shape memory effect and can restore its original shape at a certain temperature, and is used to enhance the deformation resistance of the wall material;
[0022] The phase change energy storage material is paraffin microcapsules with a particle size of 1-3 mm and a phase change temperature of 20-30°C, which can adjust the wall temperature;
[0023] The microbial curing agent comprises Bacillus and the exopolymers secreted by it, which can promote the stability and curing of the internal structure of the material;
[0024] The intelligent humidity-regulating material is a montmorillonite-sodium polyacrylate composite hydrogel, which can automatically absorb or release moisture according to the ambient humidity.
[0025] Preferably, the density of the wall material is 500-900 kg / m 3 The compressive strength is 5-10MPa, the thermal conductivity is 0.1-0.3W / (m·K), the decomposition rate of harmful pollutants such as formaldehyde and benzene in the air reaches 30-50%, and the negative ion release is 500-1000 / cm 3 , it can maintain good shape stability when the temperature changes, and its humidity regulating capacity is 20-30% of the ambient humidity change range.
[0026] Preferably, the plant fiber, recycled aggregate, aerogel microspheres, negative ion generating material, shape memory alloy fiber, phase change energy storage material, microbial curing agent, and intelligent humidity control material are all dried before mixing, with a drying temperature of 60-80° C. and a drying time of 2-4 hours, so that the moisture content of each raw material is less than 5%.
[0027] Preferably, an antioxidant is added to the mixed liquid formed by mixing the binder and the waterproofing agent. The antioxidant is vitamin C or butylated hydroxyanisole, and the added amount is 0.5-1% of the mass of the mixed liquid to improve the antioxidant performance of the material and extend the service life.
[0028] Preferably, the photocatalytic material is surface-modified before mixing, using silane coupling agent A151 for modification, the amount of silane coupling agent used is 2-5% of the mass of the photocatalytic material, and the treatment time is 1-2h to improve the dispersibility and stability of the photocatalytic material in the material.
[0029] Preferably, the method comprises the following steps:
[0030] S1. Mix plant fiber, recycled aggregate, low-carbon additive, aerogel microspheres, negative ion generating material, shape memory alloy fiber, phase change energy storage material, and microbial curing agent in proportion and stir evenly at a stirring speed of 200-500 r / min for 10-20 min.
[0031] S2, adding a binder, a waterproofing agent and a degradable polymer fiber to the mixture obtained in S1, and continuing stirring at a stirring speed of 300-600 r / min for 15-30 min to obtain a uniform mixture;
[0032] S3, uniformly dispersing the photocatalytic material in the mixed material obtained in S2, using an ultrasonic dispersion method, with an ultrasonic power of 200-500 W and an ultrasonic time of 10-20 min;
[0033] S4, adding the intelligent humidity control material to the material obtained in S3, stirring at a speed of 250-400r / min, and stirring for 10-15min;
[0034] S5. Pour the mixed material into a mold, press at a pressure of 5-10 MPa for 10-20 minutes, and after demoulding, cure in an environment with a temperature of 20-30°C and a relative humidity of 60-80% for 7-14 days.
[0035] Preferably, in step S1, the plant fiber is pretreated before use, and the pretreatment method is to soak the plant fiber in a sodium hydroxide solution with a mass fraction of 2-5% for 2-4 hours, then rinse with clean water until neutral, and dry for use;
[0036] In step S2, the binder is prepared into an aqueous solution with a mass fraction of 30-50% before being added;
[0037] In step S3, a dispersant is added during the ultrasonic dispersion process, wherein the dispersant is sodium hexametaphosphate and the amount added is 1-3% of the mass of the photocatalytic material;
[0038] In step S4, the intelligent humidity-controlling material is crushed before being added, and crushed to a particle size of 0.5-1 mm;
[0039] In step S5, a release agent is applied to the mold before use, and the release agent is vegetable oil or silicone oil.
[0040] Preferably, during the curing process, the curing environment is irradiated with ultraviolet light with an intensity of 5-10 mW / cm 2 The irradiation time is 1-2 hours per day, which promotes the curing effect of the microbial curing agent and the activity stimulation of the photocatalytic material.
[0041] (III) Beneficial technical effects
[0042] 1. Low carbon and environmentally friendly
[0043] Resource utilization and emission reduction: The recycled aggregates used in the materials, such as waste concrete, bricks and other construction waste, effectively reduce the pollution of construction waste to the environment and realize the recycling of resources. At the same time, the use of natural materials such as plant fibers replaces some traditional high-energy consumption materials, reduces carbon emissions in the production process, reduces the consumption of land resources, and significantly reduces the impact on the environment compared with traditional wall materials.
[0044] Role of low-carbon additives: Biomass carbon powder, as a low-carbon additive, not only helps to reduce the overall carbon footprint of the material, but also improves the performance of the material to a certain extent, further reflecting the application of low-carbon and environmental protection concepts in materials.
[0045] 2. Multifunctional performance
[0046] Improved thermal insulation performance: The high porosity and low thermal conductivity of aerogel microspheres greatly improve the thermal insulation performance of wall materials. This enables garden buildings to effectively reduce heat transfer, reduce energy consumption, save energy, and create a more comfortable indoor and outdoor environment for users during use.
[0047] Air purification function: The photocatalytic material composed of nano-titanium dioxide and zinc oxide can decompose harmful pollutants such as formaldehyde and benzene in the air under light conditions, with a decomposition rate of up to 30%-50%. This helps to improve the air quality around garden buildings and has positive significance for human health and the environment.
[0048] Negative ion release and environmental improvement: Tourmaline powder, as a negative ion generating material, can continuously release negative ions to the surrounding environment, with a negative ion release amount of 500-1000 / cm 3 Negative ions can absorb dust, bacteria, etc. in the air, further purify the air, and create a fresh and comfortable atmosphere.
[0049] Temperature regulation and energy saving: Phase change energy storage materials (such as paraffin microcapsules) can regulate wall temperature within a certain temperature range. By absorbing or releasing heat when the temperature changes, they can reduce the impact of indoor and outdoor temperature fluctuations on the internal temperature of the building, reduce the frequency of use of temperature control equipment such as air conditioners, and achieve energy saving effects.
[0050] Humidity regulation function: Montmorillonite-sodium polyacrylate composite hydrogel, as an intelligent humidity regulating material, can automatically absorb or release moisture according to the ambient humidity. The adjustment range can reach 20%-30% of the ambient humidity change range, which helps to maintain appropriate indoor humidity and improve living comfort.
[0051] 3. Improved mechanics and durability
[0052] Strength and stability: The binder in the material ensures good bonding between the raw materials, so that the wall material has a compressive strength of 5-10MPa, which meets the structural support requirements of the garden building wall. At the same time, the shape memory alloy fiber can enhance the deformation resistance of the wall material, so that it can still maintain good shape stability when the temperature changes or is subjected to a certain external force.
[0053] Waterproof and anti-oxidation: Silicone waterproofing agent provides good waterproof performance, preventing water from corroding the wall materials. In addition, antioxidants (such as vitamin C or butylated hydroxyanisole) added to the adhesive mixture improve the material's anti-oxidation performance, extend the service life of the wall material, and reduce maintenance costs.
[0054] 4. Beauty and plasticity
[0055] The degradable polymer fibers (such as polylactic acid fibers) in the material improve the toughness of the material, making it more plastic during processing, making it easier to shape various shapes and patterns, meeting the diverse design requirements of garden architecture, and enhancing the artistic expression of garden architecture. At the same time, the microbial curing agent can promote the stability and curing of the internal structure of the material, ensuring that the material maintains a good appearance during long-term use. DETAILED DESCRIPTION
[0056] Example 1
[0057] S1. Mix 20kg of bamboo fiber with a length of 3-10mm, 30kg of recycled aggregate with a particle size of 0.5-5mm, 15kg of biomass carbon powder as a low-carbon additive, 5kg of aerogel microspheres with a particle size of 0.5-2mm, 3kg of tourmaline powder as a negative ion generating material with a particle size of 1-5μm, 3kg of shape memory alloy fiber nickel-titanium alloy fiber with a diameter of 0.05-0.2mm, 4kg of paraffin microcapsules as a phase change energy storage material with a particle size of 1-3mm, and 5kg of microbial curing agent in proportion, stir evenly, the stirring speed is 500r / min, and the stirring time is 20min.
[0058] The photocatalytic material is a mixture of nano titanium dioxide and zinc oxide, the mass ratio of the two is 1:1, and the particle size is 20-50nm.
[0059] The plant fiber, recycled aggregate, aerogel microspheres, negative ion generating material, shape memory alloy fiber, phase change energy storage material, microbial curing agent, and intelligent humidity control material are all dried before mixing, with a drying temperature of 80° C. and a drying time of 3 hours, so that the water content of each raw material is less than 5%.
[0060] The plant fiber is pretreated before use. The pretreatment method is to soak the plant fiber in a sodium hydroxide solution with a mass fraction of 3% for 4 hours, then rinse it with clean water until it is neutral, and dry it for use.
[0061] S2. Add 15 kg of binder water glass, 8 kg of waterproofing agent polyethylhydroxysiloxane and 5 kg of degradable polymer fiber polylactic acid fiber with a diameter of 0.1-0.3 mm to the mixture obtained in S1, and continue stirring at a speed of 600 r / min for 30 min to obtain a uniform mixture.
[0062] 0.12 kg of antioxidant butylated hydroxyanisole is also added to the mixed solution formed by mixing the binder and the waterproofing agent.
[0063] The binder is prepared into a 50% by mass aqueous solution before being added.
[0064] S3. Evenly disperse 5 kg of photocatalytic material in the mixed material obtained in S2 by ultrasonic dispersion method with an ultrasonic power of 400 W and an ultrasonic time of 15 min.
[0065] The photocatalytic material was subjected to surface modification treatment before mixing, and was modified by immersion in 0.1 kg of silane coupling agent A151 for 2 hours.
[0066] During the ultrasonic dispersion process, 0.06 kg of dispersant was added, and the dispersant was sodium hexametaphosphate.
[0067] S4. Add 6 kg of the intelligent humidity-control material montmorillonite-sodium polyacrylate composite hydrogel to the material obtained in S3, with a stirring speed of 400 r / min and a stirring time of 15 min.
[0068] The intelligent humidity-control material is crushed before being added, and is crushed to a particle size of 0.5-1 mm.
[0069] S5. Pour the mixed material into the mold. Apply a mold release agent (silicone oil) to the mold before use. Press the mold under a pressure of 10 MPa for 20 minutes. After demolding, cure it in an environment with a temperature of 30°C and a relative humidity of 60% for 10 days.
[0070] During the curing process, the curing environment is irradiated with ultraviolet light with an intensity of 10mW / cm 2 The irradiation time is 1h per day.
[0071] Comparative Example 1: No aerogel microspheres were added, and the rest of the process was the same as in Example 1.
[0072] Comparative Example 2: No photocatalytic material was added, and the rest of the process was the same as in Example 1.
[0073] Comparative Example 3: No negative ion generating material is added, and the remaining processes are the same as those in Example 1.
[0074] Comparative Example 4: No intelligent humidity-controlling material is added, and the rest of the process is the same as in Example 1.
[0075] Table 1
[0076]
[0077] As can be seen from Table 1, the thermal conductivity, harmful pollutant decomposition performance, negative ion release, and humidity control ability of Example 1 are all superior to those of the comparative example. The addition of aerogel microspheres can effectively improve the thermal conductivity, the addition of photocatalytic materials can effectively improve the harmful pollutant decomposition performance, the addition of negative ion generating materials can increase the negative ion release, and the addition of intelligent humidity control materials can effectively improve the moisture absorption capacity.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low-carbon wall material for garden buildings, characterized in that: The invention comprises the following raw materials in parts by weight: 20-40 parts of plant fiber, 30-50 parts of recycled aggregate, 10-20 parts of binder, 5-15 parts of low-carbon additive, 2-8 parts of waterproofing agent, 3-8 parts of aerogel microspheres, 2-6 parts of photocatalytic material, 3-7 parts of negative ion generating material, 5-10 parts of degradable polymer fiber, 2-5 parts of shape memory alloy fiber, 3-6 parts of phase change energy storage material, 2-5 parts of microbial curing agent, 3-8 parts of intelligent humidity control material; The plant fiber has a length of 3-10 mm and is selected from one or more of hemp fiber, bamboo fiber and straw fiber; The particle size of the recycled aggregate is 0.5-5 mm, and it is made by crushing waste concrete and bricks; The binder is an environmentally friendly inorganic binder, selected from one or more of water glass and phosphate binders; The low-carbon additive is biomass carbon powder, the particle size of which is less than 0.1 mm and the specific surface area is 200-500 m 2 / g; The waterproofing agent is an organosilicon waterproofing agent; The aerogel microspheres have a particle size of 0.5-2 mm, a porosity of 80-95%, and are mainly composed of silicon dioxide aerogel; The photocatalytic material is a mixture of nano titanium dioxide and zinc oxide, the mass ratio of the two is 1-3:1, and the particle size is 20-50nm; The negative ion generating material is tourmaline powder with a particle size of 1-5 μm; The degradable polymer fiber is polylactic acid fiber with a diameter of 0.1-0.3 mm; The shape memory alloy fiber is a nickel-titanium alloy fiber with a diameter of 0.05-0.2 mm and a shape memory effect; The phase change energy storage material is paraffin microcapsules with a particle size of 1-3 mm and a phase change temperature of 20-30°C, which can adjust the wall temperature; The microbial solidifying agent comprises Bacillus and its secreted extracellular polymers; The intelligent humidity-regulating material is a montmorillonite-sodium polyacrylate composite hydrogel, which can automatically absorb or release moisture according to the ambient humidity.
2. A low-carbon wall material for garden buildings according to claim 1, characterized in that: The density of the wall material is 500-900kg / m 3 The compressive strength is 5-10MPa, the thermal conductivity is 0.1-0.3W / (m·K), the decomposition rate of harmful pollutants such as formaldehyde and benzene in the air reaches 30-50%, and the negative ion release is 500-1000 / cm 3 , it can maintain good shape stability when the temperature changes, and its humidity regulating capacity is 20-30% of the ambient humidity change range.
3. The low-carbon wall material for garden buildings according to claim 1, characterized in that: The plant fiber, recycled aggregate, aerogel microspheres, negative ion generating material, shape memory alloy fiber, phase change energy storage material, microbial curing agent and intelligent humidity control material are all dried before mixing, with a drying temperature of 60-80° C. and a drying time of 2-4 hours, so that the water content of each raw material is less than 5%.
4. The low-carbon wall material for garden buildings according to claim 1, characterized in that: An antioxidant is also added to the mixed liquid formed by mixing the binder and the waterproofing agent. The antioxidant is vitamin C or butylated hydroxyanisole, and the added amount is 0.5-1% of the mass of the mixed liquid.
5. The low-carbon wall material for garden buildings according to claim 1, characterized in that: The photocatalytic material is subjected to surface modification treatment before mixing, and is modified by using silane coupling agent A151, the amount of silane coupling agent used is 2-5% of the mass of the photocatalytic material, and the treatment time is 1-2 hours.
6. A method for preparing a low-carbon wall material for a garden building as claimed in claims 1 to 5, characterized in that: The following steps are involved: S1. Mix plant fiber, recycled aggregate, low-carbon additive, aerogel microspheres, negative ion generating material, shape memory alloy fiber, phase change energy storage material, and microbial curing agent in proportion and stir evenly at a stirring speed of 200-500 r / min for 10-20 min. S2, adding a binder, a waterproofing agent and a degradable polymer fiber to the mixture obtained in S1, and continuing stirring at a stirring speed of 300-600 r / min for 15-30 min to obtain a uniform mixture; S3, uniformly dispersing the photocatalytic material in the mixed material obtained in S2, using an ultrasonic dispersion method, with an ultrasonic power of 200-500 W and an ultrasonic time of 10-20 min; S4, adding the intelligent humidity control material to the material obtained in S3, stirring at a speed of 250-400 r / min, and stirring for 10-15 min; S5. Pour the mixed material into a mold, press at a pressure of 5-10 MPa for 10-20 minutes, and after demoulding, cure in an environment with a temperature of 20-30°C and a relative humidity of 60-80% for 7-14 days.
7. The method for preparing a low-carbon wall material for a garden building according to claim 6, characterized in that: In step S1, the plant fiber is pretreated before use. The pretreatment method is to soak the plant fiber in a sodium hydroxide solution with a mass fraction of 2-5% for 2-4 hours, then rinse it with clean water until it is neutral, and dry it for use; In step S2, the binder is first prepared into an aqueous solution with a mass fraction of 30-50% before being added; In step S3, a dispersant is added during the ultrasonic dispersion process, wherein the dispersant is sodium hexametaphosphate and the amount added is 1-3% of the mass of the photocatalytic material; In step S4, the intelligent humidity-controlling material is crushed before being added, and crushed to a particle size of 0.5-1 mm; In step S5, a release agent is applied to the mold before use, and the release agent is vegetable oil or silicone oil.
8. The method for preparing a low-carbon wall material for a garden building according to claim 6, characterized in that: During the curing process, the curing environment is irradiated with ultraviolet light with an intensity of 5-10mW / cm 2 The irradiation time is 1-2h per day.